2015
DOI: 10.1158/0008-5472.can-13-3629
|View full text |Cite
|
Sign up to set email alerts
|

Foretinib Is Effective Therapy for Metastatic Sonic Hedgehog Medulloblastoma

Abstract: Medulloblastoma is the most common malignant pediatric brain tumor, with metastases present at diagnosis conferring a poor prognosis. Mechanisms of dissemination are poorly understood and metastatic lesions are genetically divergent from the matched primary tumor. Effective and less toxic therapies that target both compartments have yet to be identified. Here, we report that the analysis of several large nonoverlapping cohorts of patients with medulloblastoma reveals MET kinase as a marker of sonic hedgehog (S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 50 publications
2
52
1
Order By: Relevance
“…In a preclinical study, foretinib was reported to be able to penetrate the BBB (the penetration of the drug in the brain was 14%) and reduce the growth of medulloblastoma cells in an orthotopic CNS dissemination model (35). In line with these results, we demonstrated that foretinib inhibits the tumor progression due to KM12SM-ER cells in a brain metastasismimicking model.…”
Section: Discussionsupporting
confidence: 85%
“…In a preclinical study, foretinib was reported to be able to penetrate the BBB (the penetration of the drug in the brain was 14%) and reduce the growth of medulloblastoma cells in an orthotopic CNS dissemination model (35). In line with these results, we demonstrated that foretinib inhibits the tumor progression due to KM12SM-ER cells in a brain metastasismimicking model.…”
Section: Discussionsupporting
confidence: 85%
“…[104] This inhibition blocked the EMT induced by VEGF ablation in a GBM mouse model [105] and induced an effective decrease in MB cell migration and invasion. [106,107] Stromal cell derived factor (SDF-1) or CXCL2 and its chemokine receptor CXCR4 can induce EMT in GBM via activation of PI3K/AKT and extracellular-signal-regulated kinases (ERK) pathways, and its inhibition suppressed EMT in glioma cell lines by upregulating E-cadherin. [108] However, single agents targeting the PAM pathway have been reported to be an inefficient approach in MB and to increase invasion in the surviving fraction of GBM.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%
“…For example, it was reported that the rat glioma model could be induced by implantation of cultured glioma cells (Cell-derived xenograft: CDX) [3, 4] and transplanted tumor fragments (Patient-derived xenograft: PDX) [5]. Medulloblastom was regarded as the most common malignant brain tumor in pediatrics with a poor prognosis and in vivo investigation; it was often induced by transplantation of chemically modified human medulloblastoma cells such as Daoy, ONS76 and D425 [6]. Although these animal models have the advantage of making the tumor models for a short time and are widely used for the study of brain tumors, they do not comprehensively recapitulate human neoplasms and often caused the inhibitory tumor-host immunoresponses [7, 8].…”
Section: Current Status: Animal Models Of Brain Tumorsmentioning
confidence: 99%